Invisible : Unsolved - Book 2 - Patterson, James, 1947-; Ellis, David, 1967- (New York : Grand Central Publishing, 2019)
When a series of suspicious fatal accidents baffle FBI agent Dockery, she finds her investigation complicated by her ex and a killer who is somehow one step ahead.
Keywords: United States. -- Federal Bureau of Investigation -- Officials and employees; Fiction; Government investigators; Fiction; Murder -- Investigation; Fiction; Mystery fiction; Suspense fiction